Evaluating the success rates and effectiveness of surgical and orthodontic interventions for impacted canines: a systematic review of surgical and orthodontic interventions and a case series - Antonio Mancini; Fabrizio Chirico; Giuseppe Colella; Fabio Piras; Valeria Colonna; Pierluigi Marotti; Claudio Carone; Alessio Danilo Inchingolo; Angelo Michele Inchingolo; Francesco Inchingolo; Gianna Dipalma (BMC Oral Health)
Abstract Objectives The goal is to gather more information on orthodontic traction of impacted canines in the arch or their extraction. Methods We focused our search on English-language papers published between January 1, 2004, and July 24, 2024 in PubMed, Scopus, and Web of Science that were relevant to our topic. The search strategy employed the Boolean terms "impacted" AND "canine". In addition to the overview, this article discusses a number of clinical instances involving canine disinclusion. Results The study analyzed 2748 papers from databases like Web of Science, PubMed, and Scopus, resulting in 1455 articles after eliminating duplicates. After examining titles and abstracts, 897 entries were removed. The remaining 558 papers were confirmed, with 543 items removed due to being off-topic. The study includes a qualitative analysis of the 15 final articles. Conclusions This article concludes that both extraction and orthodontic traction are effective treatments for impacted canines, with the choice depending on patient-specific factors. Advances in surgical techniques and imaging technologies have improved outcomes, while a multidisciplinary, patient-centered approach remains essential. Future research should focus on refining treatment selection criteria and integrating genetic and technological advancements.